Korelasi Kecerdasan Emosional dan Spiritual dengan Pengetahuan Hadis pada Mahasiswa Prodi IAT UIN Ar-Raniry Banda Aceh - Siti Hajril Masyithah; Maizuddin Maizuddin; Nurkhalis Nurkhalis (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2019)
This paper aims to determine the relationship between emotional intelligence and spiritual intelligence with knowledge of hadith about Islam, faith and ihsan in students of the Qur'an and Tafsir Study Program, Faculty of Ushuluddin and Philosophy (IAT FUF) UIN Ar-Raniry Banda Aceh. This research is quantitative with the type of correlation research. Based on the results of the study, shows: first, there is a positive and significant relationship between emotional intelligence and spiritual intelligence with the results of hadith knowledge about Islam, faith and ihsan in students of IAT FUF UIN Ar-Raniry Banda Aceh Study Program. The correlation between emotional intelligence and spiritual intelligence is directly proportional to hadith knowledge. With a correlation coefficient level of 0.65 in the strong category with a coefficient of determination (D) = 42%, the higher the level of knowledge of hadith about Islam, faith and ihsan among students, the higher the level of emotional intelligence and spiritual intelligence possessed by students the. Second, practical knowledge of hadith about Islam, faith and ihsan encourages students to motivate themselves, control emotions in social interactions and interpret the learning process as worship. Tulisan ini bertujuan untuk mengetahui hubungan kecerdasan emosional dan kecerdasan spiritual dengan pengetahuan hadis tentang Islam, iman dan ihsan pada mahasiswa Prodi Ilmu Alquran dan Tafsir Fakultas Ushuluddin dan Filsafat (IAT FUF) UIN Ar-Raniry Banda Aceh. Penelitian ini bersifat kuantitatif dengan jenis penelitian korelasi. Berdasarkan hasil penelitian menunjukkan: pertama, terdapat hubungan yang positif dan signifikan antara kecerdasan emosional dan kecerdasan spiritual dengan hasil pengetahuan hadis tentang Islam, iman dan ihsan pada mahasiswa Prodi IAT FUF UIN Ar-Raniry Banda Aceh. Korelasi antara kecerdasan emosional dan kecerdasan spiritual berbanding lurus dengan pengetahuan hadis. Dengan tingkat koefisien korelasi sebesar 0,65 pada kategori kuat dengan koefisien determinasi (D) = 42%, semakin tinggi tingkat pengetahuan hadis tentang Islam, iman dan ihsan di kalangan mahasiswa, maka semakin tinggi pula tingkat kecerdasan emosional dan kecerdasan spiritual yang dimiliki oleh mahasiswa tersebut. Kedua, secara praktis pengetahuan hadis tentang Islam, iman dan ihsan mendorong mahasiswa untuk memotivasi diri, mengendalikan emosi dalam interaksi sosial dan memaknai proses pembelajarannya sebagai ibadah.